Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-02-27T20:34:40+01:00
Bonsoir, 


1) Développer puis réduire E :

E= (x + 2)(2x - 5) - (x + 2)(5x - 1)
E= 2x² - 5x + 4x - 10 - (5x² - x + 10x - 2)
E= 2x² - x - 10 - 5x² + x - 10x + 2
E= - 3x² - 10x - 8

2) Factoriser E : 

E= (x + 2)(2x - 5) - (x + 2)(5x - 1)
E= (x + 2)(2x - 5 - 5x + 1)
E= (x + 2)(-3x - 4)

3) Calculer E lorsque x = - 3 :

E= (x + 2)(2x - 5) - (x + 2)(5x - 1)
E= (- 3 + 2)(2 X (-3) - 5) - (- 3 + 2)(5 X (-3) - 1)
E= - 1 X (- 11) - (- 1 X (-16))
E= 11 - 16 
E = - 5

4) Calculer E lorsque x = 2 :

E= (x + 2)(2x - 5) - (x + 2)(5x - 1)
E= (2 + 2)(2 X 2 - 5) - (2 + 2)(5 X 2 - 1)
E= 4 X (- 1) - 4 X 9
E= - 4 - 36
E = - 40

Bonne soirée! :)



oooh merci beaucoup :D
De rien! (encore) :)